The Association between Body Mass Index (BMI) and back or leg pain in patients with spinal conditions - Segar, A; Urban, J; Fairbank, J; Judge, A (2016)
Study design: Prospective observational study Objective: To identify the relationship between obesity, quantified by body mass index (BMI), and both back and leg pain in spinal patients. Summary of Background Data: Obesity and back pain are massive public health problems. Given the poor correlation between pain and a pathological change in the spine, further investigation is required into other, non-pathological, predictors such as obesity. Methods: The Genodisc Study was one of the largest cross-sectional studies of patients presenting to tertiary spinal units and recruited from six centres in four European countries. In total, 2636 patients were recruited over a 5-year period between 2008 and 2013. Both back and leg pain were scored by patients in the range of 0 to 10. Linear regression was used to model the relationship between BMI and pain. Potential confounders included in the model were: age, Zung Depression score, episodes of sport, gender, disability benefit, family history, previous surgery, smoking status, work type, clinical diagnosis and relevant co-morbidities. Back and leg pain outcomes were modelled separately. Results: The study included 1160 men and 1349 women with a mean age of 50.9 years and mean BMI of 27.2kg/m2. In our fully adjusted model, a 5-point increase in BMI was associated with greater leg (0.19 units [95% CI 0.08,0.31]) but not back (0.10 units [95% CI -0.02,0.22]) pain scores. Although this relationship was statically significant, given the small magnitude of the relationship, the clinical significance is limited. Similarly, female gender, heavy workload, rheumatoid arthritis, previous spine surgery and depression were associated with higher back and leg pain. Conclusion: In this large observational study of spine patients presenting to tertiary European centres, obesity, as measured by increased body mass index, was associated with greater leg pain.